„If the images of the present don’t change, then change the images of the past“: – Zur Exposition Coloniale Internationale, Paris 1931 - Kuster, Brigitta (Comparativ, 2009)
The highly ambivalent modernist discourse about a progressive colonialism (“colonialisme de progrès“) climaxes with the “Exposition Coloniale Internationale“ in 1931. This contribution argues that its struggle for a ‚partnership‘ between the colonial population and the simultaneous supreme power of the metropolis (in a political sense as well as in an economical and cultural) prefigures the decay of the colonial era. The ambivalences between “citoyen“ and “sujet“ are discussed as a crisis of the interpellation by “La Plus Grande France“ which draws through the field of the visible and thus the spectacular within the “exhibition complex.“ By means of contemporary photographs and police files, both pointing especially to the role of the „indigènes“ working and performing on the exhibition ground, this contribution tracks the emerging formation of anti-colonial movements and resistances.